Mainstreaming precast and block hempcrete—a carbon sequestering solution for the built environment - Pandwe Gibson (Academia Materials Science)
The International Residential Code (IRC) appendix, which offers guidance on acceptable building materials, was updated in 2023 to include hempcrete for the first time in its 2024 version. Hempcrete, a blend of hemp hurd, lime, and water, has emerged as a sustainable and carbon-negative building material with promising applications in the construction industry. This review article provides a comprehensive overview of hempcrete, starting with its historical roots and the basic science behind its composition. Hemp was used in Rome as far back as Julius Caesar’s time and in the sixth century when France was still Gaul. Lime building construction dates to before its use in the pyramids and can be found in ancient Africa, Persia, Rome, and throughout many indigenous cultures. Exploring the role of lime in enhancing the material’s properties, we delve into the reasons behind its inclusion in hempcrete formulations. Opportunities and challenges in the adoption of hempcrete are discussed, highlighting its potential to revolutionize the construction sector. The evolution of curing techniques for hempcrete, from traditional methods to modern innovations, is examined, offering insights into future advancements. We explain why the utility of hemp has historically been overshadowed by a false narcotics narrative and association. We codify hempcrete’s performance to underscore its environmental benefits and economic viability. We explore how lime, CO2, and structural components can increase commercial viability and create the scale necessary for the United Nations Intergovernmental Panel on Climate Change’s (IPCC) call for nations to maintain the global temperature increase below 1.5°C and net zero by 2050 while tackling the global housing crisis. Thus, this article serves as a valuable resource for researchers, architects, and policymakers interested in advancing adoption of sustainable construction practices.